Relative depolarization of the black hole photon ring in GRMHD models of Sgr A* and M87*. Issue 3 (22nd March 2021) - Jiménez-Rosales, A; Dexter, J; Ressler, S M; Tchekhovskoy, A; Bauböck, M; Dallilar, Y; de Zeeuw, P T; Drescher, A; Eisenhauer, F; von Fellenberg, S; Gao, F; Genzel, R; et al.
ABSTRACT: Using general relativistic magnetohydrodynamic simulations of accreting black holes, we show that a suitable subtraction of the linear polarization per pixel from total intensity images can enhance the photon ring feature. We find that the photon ring is typically a factor of ≃2 less polarized than the rest of the image. This is due to a combination of plasma and general relativistic effects, as well as magnetic turbulence. When there are no other persistently depolarized image features, adding the subtracted residuals over time results in a sharp image of the photon ring. We show that the method works well for sample, viable GRMHD models of Sgr A* and M87*, where measurements of the photon ring properties would provide new measurements of black hole mass and spin, and potentially allow for tests of the 'no-hair' theorem of general relativity.